2012
DOI: 10.1016/b978-0-12-394316-3.00003-x
|View full text |Cite
|
Sign up to set email alerts
|

SLC4A Transporters

Abstract: SLC4A gene family proteins include bicarbonate transporters that move HCO3− across the plasma membrane and regulate intracellular pH and transepithelial movement of acid–base equivalents. These transporters are Cl/HCO3 exchangers, electrogenic Na/HCO3 cotransporters, electroneutral Na/HCO3 cotransporters, and Na+-driven Cl/HCO3 exchanger. Studies of the bicarbonate transporters in vitro and in vivo have demonstrated their physiological importance for acid–base homeostasis at the cellular and systemic levels. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 133 publications
(158 reference statements)
0
20
0
1
Order By: Relevance
“…In initial pilot studies of intact red cell membranes, one of our primary targets is the protein known as anion exchanger 1 (AE1) or band 3, which is the most abundant red cell membrane protein with about 1.2 million copies per cell [87]. A large portion of the protein is embedded in the lipid bilayer, but about half of the mass is in the cytoplasm [88]. We have identified cross-links between several AE1 cytoplasmic domains, and structural models for the protein are currently being developed.…”
Section: Further Enhancing Zero-length Cx-msmentioning
confidence: 99%
“…In initial pilot studies of intact red cell membranes, one of our primary targets is the protein known as anion exchanger 1 (AE1) or band 3, which is the most abundant red cell membrane protein with about 1.2 million copies per cell [87]. A large portion of the protein is embedded in the lipid bilayer, but about half of the mass is in the cytoplasm [88]. We have identified cross-links between several AE1 cytoplasmic domains, and structural models for the protein are currently being developed.…”
Section: Further Enhancing Zero-length Cx-msmentioning
confidence: 99%
“…They have also developed a flexible membrane that can withstand the high amounts of shear stress involved in squeezing through capillaries (Romero et al, 2004). The most abundant protein in the erythrocyte membrane is anion exchanger 1 (AE1) with approximately one million copies per cell (Burton and Bruce, 2011), also known as band 3, which is encoded by the SLC4A1 gene (Choi, 2012). An isoform of AE1 is expressed in the kidney and the related homologs, AE2 and AE3, serve similar functions in most other tissues (Alper, 2009; Bonar and Casey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In distal tissues, carbon dioxide diffuses across the erythrocyte membrane, where the abundant cytoplasmic protein carbonic anhydrase converts it plus a water molecule to a proton and a bicarbonate ion (HCO 3 − ). AE1 actively transports the bicarbonate out of the cell with neutral exchange of chloride (Cl − ) ions into the cell (Choi, 2012). Several crystal structures of the cytoplasmic domain (Shnitsar et al, 2013; Zhang et al, 2000), as well as a structure of the ion channel domain (Arakawa et al, 2015), have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Band 3 (SLC4A1), a membrane protein of 911 amino acids, belongs to the SLC4A family of HCO 3 — (and CO 3 2- ) transporters ( Choi, 2012 ; Romero et al, 2013 ). Band 3 is also known as anion exchanger (AE1), as band 3-mediated HCO 3 — transport is coupled at a 1:1 ratio with an anti-parallel flux of Cl — , the most abundant anion physiologically.…”
Section: Introductionmentioning
confidence: 99%